Characteristic Isolation of Bacteria in Lake Water on Campus-A of UIN Sulthan Thaha Saifuddin Jambi - Latusi Anggriani; Aini Qomariah Manurung; Andina Dwiana Marsa; Nisma Hariyanti Ritonga; Cheryska Alinza; Nuraisyah Gustri Anggrai Ningsih; Muhammad Arif Januarda Saputra (Universitas Labuhanbatu, 2025)
Background: Water bodies are highly susceptible to contamination from various sources, including domestic, agricultural, and industrial waste. These contaminants often introduce pathogenic microorganisms such as Escherichia coli and Salmonella sp., which pose significant risks to human and animal health. Despite this, bacteria also play a vital role in supporting aquatic ecosystems by facilitating the decomposition of organic matter. Methodology: This study was conducted with the objective of isolating and characterizing bacterial species present in the waters of Campus A Lake. Sampling was carried out by collecting water from several points within the lake. Bacterial isolation was performed using the serial dilution technique, followed by inoculation on Nutrient Agar (NA) media and incubation at 37 °C for 24 hours. The characterization phase included morphological observation of colonies, Gram staining, and biochemical tests such as oxidase reactions. Findings: The study successfully isolated three distinct bacterial colonies. One isolate exhibited a rod-shaped (bacillus) morphology, while the remaining two showed a spherical (coccus) form. All isolates tested Gram-negative, evidenced by the pink coloration after staining. Importantly, most of the isolates demonstrated an ability to break down organic material, indicating their usefulness in environmental cleanup. Additionally, the introduction of Eco Enzyme into lake water positively influenced the microbial ecosystem by promoting the growth of beneficial decomposers like Bacillus sp. and Lactobacillus sp., while simultaneously suppressing pathogenic bacteria. Contribution: These findings provide valuable insight for future water quality management and the development of effective, eco-friendly bioremediation strategies.